Constituent assembly elections in Zugdidi Mazra - Lashkhia, Bakur (COLLECTION OF SCIENTIFIC WORKS OF SOKHUMI UNIVERSITY, 2025)
This article studies the elections of the Constituent Assembly of the Democratic Republic of Georgia in Zugdidi Mazra, which has not been studied to date. On November 19, 1917, the Georgian National Congress opened, and on November 21, the National Congress elected the “Georgian National Council,” which was tasked with convening the Constituent Assembly. On June 24, 1918, by a decision taken at the 12th meeting of the Georgian National Council, the Georgian government resigned and, until the convening of the Constituent Assembly, its duties were performed by a provisional government. In October 1918, the National Council was renamed the Parliament of Georgia, which approved the Statute for the Constituent Assembly elections on November 22 of the same year. On January 10, 1919, the Parliament of Georgia adopted a decision to amend the Statute for the Constituent Assembly elections. On January 3, 1919, according to the decision taken at the 77th session of the Parliament of Georgia, the elections to the Constituent Assembly were scheduled for February 14-16. Based on the above decision, on January 16, 1919, under the leadership of the Zugdidi City Council, the Election Commission of the Constituent Assembly was formed. The work discusses the elections held in the Zugdidi district and their results in stages. The results of the elections of the Constituent Assembly held in the Zugdidi district on February 14-17, 1919 were discussed by the Zugdidi Council Commission on February 24. The results were distributed among political parties as follows: Georgian Social-Democratic Workers’ Party - 15,149 votes; Georgian National-Democratic Party - 2,414 votes; Georgian Socialist-Revolutionary Party - 8,070 votes; Georgian Socialist-Federalist Revolutionary Party - 2,315 votes; Georgian National Party - 7 votes; Socialist Federalist Party of Georgia - 57 votes; Union of Independent Non-Parties - 1 vote. The paper analyzes the elections of the Constituent Assembly in the Zugdidi region and concludes that the elections in this particular part of Georgia were held in full compliance with democratic principles. The paper analyzes the elections of the Constituent Assembly in the Zugdidi region and concludes that the elections in this specific part of Georgia were held in full compliance with democratic principles.